Analisis Pengaruh Kualitas Laba Terhadap Nilai Perusahaan - esty apridasari (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2018)
The information of earnings contained in the financial statement is expected to minimize the interest conflicts occuring within agency theory. This study aims to obtain empirical evidence related to the influence of earnings quality on firm value. The population of this research is manufacturing company listed on the Indonesia Stock Exchange in 2014-2016 with 66 manufacturing companies and 175 observations as sample. Determination of the sample in this study is carried out by purposive sampling method. Earnings quality is measured by Earnings Response Coefficient (ERC) and the firm value is measured with Price Book Value (PBV). Testing hypotheses using regression analysis. The results show that earnings quality has been proven to have positive influence on firm value with significant value 0,000. This show that in order to increase the firm value, it could increase its earnings quality